Dynamic Hip Screw with Trochanter-Stabilizing Plate Compared with Proximal Femoral Nail Antirotation as a Treatment for Unstable AO/OTA 31-A2 and 31-A3 Intertrochanteric Fractures. (19th August 2020) - Fu, Chun-Wei; Chen, Ji-Ying; Liu, Yueh-Ching; Liao, Kuang-Wen; Lu, Yung-Chang
Abstract : Background . The dynamic hip screw (DHS) with the addition of an angular stable trochanter-stabilizing plate (TSP) has been considered the ideal treatment for the unstable intertrochanteric fracture type. However, there have been few comparisons between DHS+TSP augmentation with intramedullary (IM) nailing. The aim of this retrospectively registered study was to compare the clinical outcomes of patients with the unstable type of intertrochanteric fractures treated with DHS+TSP or IM nailing (proximal femoral nail antirotation (PFNA)). Methods . From June 2013 to April 2018, 358 patients with proximal femur fracture AO/OTA type 31A2 and 31A3 treated with PFNA or DHS+TSP and followed for ≥10 months postoperatively were included. The surgical-dependent outcome evaluation included the operation time, intraoperative blood loss, postoperative decrease in hemoglobin, and blood transfusion amount. Functional status was also measured. Radiographic findings and postoperative complications were recorded and analyzed. Result . The operation time was significantly shorter in the DHS+TSP group than that in the PFNA group for both A2 and A3 fractures (A2 type: 84.0 vs.96.4 min; p < 0.05 ; A3 type: 102.4 vs.116.1 min; p < 0.05 ). Postoperative decrease in hemoglobin was more significant in the PFNA group than that in the DHS+TSP group for both fracture types (A2 type: −1.88 vs. −1.29 (mg/dL); p < 0.05 ; A3 type: −1.63 vs. −1.04 (mg/dL); p < 0.05 ). However, the patients treated with DHS+TSP had significantly more residual pain than those treated with PFNA during the final follow-up (Visual Analog Scale score, A2 type: 28.4 vs.23.2; p < 0.05 ; A3 type: 27.5 vs.23.6; p < 0.05 ) and complained of greater implant irritation. Conclusion . We found that DHS+TSP was associated with less operation time and less postoperative decrease in hemoglobin but more residual pain and implant irritation than those of PFNA. As a treatment for unstable intertrochanteric fracture, DHS+TSP provided ideal surgical outcomes which were not inferior to the PFNA.